2003
DOI: 10.1007/s00429-002-0296-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphological study of the lingual papillae and their connective tissue cores of the koala

Abstract: The stereo structure of each lingual papilla of the koala has a similar structure to that of various other animal species: the koala has a lingual prominence (intermolar prominence) with larger filiform papillae. (A lingual prominence is a characteristic in herbivorous animals.) The external form and connective tissue core (CTC) of the filiform papillae of koalas consist of one large main process and several smaller accessory processes. (These are similar to carnivorous animals.) Fungiform CTC have a thick dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 21 publications
(18 reference statements)
2
52
0
3
Order By: Relevance
“…Furthermore, in the genus Didelphis, elongated mucosal folds with numerous, irregular, fingerlike projections were identified on the posterolateral borders where foliate papillae are normally found in other species. Kobayashi et al (2003) reported that the external form and connective tissue core of the filiform papillae of koalas consist of one large main process and several smaller accessory ones. Three vallate papillae were identified: one central midline (round type) and two laterally located (slit-like type) ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the genus Didelphis, elongated mucosal folds with numerous, irregular, fingerlike projections were identified on the posterolateral borders where foliate papillae are normally found in other species. Kobayashi et al (2003) reported that the external form and connective tissue core of the filiform papillae of koalas consist of one large main process and several smaller accessory ones. Three vallate papillae were identified: one central midline (round type) and two laterally located (slit-like type) ones.…”
Section: Discussionmentioning
confidence: 99%
“…In the order Marsupialia, there have been a few scanning electron microscopy (SEM) studies on the tongues of opossum (Krause and Cutts, 1982), koala (Kobayashi et al, 2003), red kangaroo (Emura et al, 2004), sugar glider (Emura, 2011) and brush-tailed rat kangaroo (Emura et al, 2014). Such studies have revealed variations in the morphology and distribution of papillae on the dorsal lingual surface among animal species.…”
mentioning
confidence: 99%
“…Essa diferença morfológica pode ser devida ao tipo de alimentação, que pode contribuir para a alteração no formato das papilas em contato com o alimento durante a ingestão e mastigação. Já Agungpriyono et al (1995), Kobayashi et al (2003) e Benetti et al (2009) não relatam a presença desse tipo de papila na língua das espécies estudadas.…”
Section: Discussionunclassified
“…As papilas ϐiliformes, cônicas e lentiformes possuem funções mecânicas, enquanto que as fungiformes, valadas e foliáceas possuem função gustativa (Konig & Liebich 2004). Diversos artigos descrevem as características estruturais e ultraestruturais das papilas linguais de roedores (Hume & Potten 1976, Kobayashi et al 2003, felinos (Boshell & Wilborn 1982), equinos e ruminantes (Chamorro et al 1986, Paz Cabello et al 1988, ruminantes selvagens (Agungprivono et al 1995), caninos (Iwasaki & Miyata 1989), queixada ), bicho-preguiça (Benetti et al 2009) e koala (Kobayashi et al 2003), entre outros.…”
Section: Introductionunclassified
“…The distribution of three vallate papillae in the form of a triangle in the Egyptian fruit bat is similar to frugivorous species (Emura et al, 2001(Emura et al, , 2002, although the number of vallate papillae in bats varies; the long-nosed bat has four of them, whereas the bats from the Vespertilionidae, Rhinolophidae, Hipposideridae families and the European free-tailed bats have two vallate papillae, and the blooddrinking Desmodus rotundus has none (Greenbaum and Phillips, 1974). It should be noted that the arrangement of three vallate papillae is commonly observed in marsupials which are also an older mammalian order (Kubota et al, 1963;Krause and Cutts, 1982;Abe et al, 2001;Kobayashi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%